Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1146/annurev-publhealth-031811-124646
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on Healthy Eating

Abstract: Large nutritional epidemiology studies, with long-term follow-up to assess major clinical end points, coupled with advances in basic science and clinical trials, have led to important improvements in our understanding of nutrition in primary prevention of chronic disease. Although much work remains, sufficient evidence has accrued to provide solid advice on healthy eating. Good data now support the benefits of diets that are rich in plant sources of fats and protein, fish, nuts, whole grains, and fruits and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
148
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 157 publications
0
148
0
7
Order By: Relevance
“…For example, diets with fewer animal-sourced foods typically include more nuts and whole grains (30,31), which evidence suggests have health benefits and are likely to increase the number of avoided deaths (4). Similarly, it is known that salt and sugar ingested in sugary drinks affect health (4), but comparative international data on their effects is insufficient to include in our models whereas the health impacts of other food groups (for example dairy) is inconclusive (35). Wherever possible, we have placed confidence estimates around our results, but we are aware that other sources of uncertainty exist that we have not been able to treat.…”
Section: Discussionmentioning
confidence: 99%
“…For example, diets with fewer animal-sourced foods typically include more nuts and whole grains (30,31), which evidence suggests have health benefits and are likely to increase the number of avoided deaths (4). Similarly, it is known that salt and sugar ingested in sugary drinks affect health (4), but comparative international data on their effects is insufficient to include in our models whereas the health impacts of other food groups (for example dairy) is inconclusive (35). Wherever possible, we have placed confidence estimates around our results, but we are aware that other sources of uncertainty exist that we have not been able to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate diet may also contribute to other RFs, such as arterial hypertension (AH), obesity, and malnutrition. Prospective 18 , case-control 19 , and other types of studies 20 have indicated that consumption of fruits and vegetables is associated with the prevention of cardiovascular diseases, some cancers, and neural tube defects, which has been explained by the content of micronutrients such as potassium, lycopene, folic acid, carotenoids, fibers, polyphenols, water, and low caloric density. Because it is a modifiable factor, it becomes important to adopt public policies that may interfere with behaviors, such as the publication of the Food Guide for the Brazilian Population (2014) 21 and voluntary agreements for the reduction of sodium and trans fats in industrialized foods 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ervin had similar findings 20 . High intake of whole grains reduces constipation and is associated with lower risk of developing cardiovascular disease, diabetes and diverticulitis 33 . Munter et al 34 reported an inverse association between consumption of whole grains and the risk of type 2 diabetes, and found that the increment of two servings/day decreased the risk of the disease by 21%.…”
Section: Discussionmentioning
confidence: 99%